NILAI-NILAI UNIVERSAL QS. AL-MUJÂDALAH [58]: 11: KAJIAN HERMENEUTIKA DOUBLE MOVEMENT FAZLUR RAHMAN - Muhammad Arsyad (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2023)
This study examines the universal values contained in QS. al-Mujâdalah [58]: 11 using Fazlur Rahman's double movement hermeneutics approach. Using library research methods, this study analyzes how the double movement method can interpret the verse's meaning from its historical context to find universal moral values applicable to contemporary life. The results show that QS. al-Mujâdalah [58]: 11 contains two main universal values: social ethics through the command to create inclusivity in assemblies, and respect for knowledge as indicated by the elevated status of knowledgeable people. Through the double movement approach, these values can be contextualized in modern settings such as educational access, workplace equality, and knowledge development integration. This research demonstrates that the Qur'anic moral message remains flexible and applicable across different situations while maintaining its essential values.